Nihonogomphus schorri sp. nov. from Huu Lien Nature Reserve, Lang Son Province, Vietnam (Odonata: Gomphidae) - Do, Manh Cuong; Karube, Haruki (Zootaxa, 2011)
A new species Nihonogomphus schorri Do & Karube, sp. nov. is described on the basis of male specimens collected from Huu Lien Nature Reserve, Lang Son Province, northern Vietnam. It is close to the Chinese species N. bequaerti Chao, 1954 due to the similarity of hamules, anal appendages and vesicle, but is easy toseparate from that species by the vesica spermalis structure and body markings.